The characteristics and outcomes of critically Ill patients with COVID-19 who received systemic thrombolysis for presumed pulmonary embolism: an observational study - So, Matsuo (J Thromb Thrombolysis, 2021)
Coronavirus disease 2019 (COVID-19) is associated with abnormal hemostasis, autopsy evidence of systemic microthrombosis, and a high prevalence of venous thromboembolic disease. Tissue plasminogen activator (tPA) has been used in patients with critically ill COVID-19 with high clinical suspicion of pulmonary embolism (PE). A retrospective cohort study of 6095 hospitalized COVID-19 patients at 5 acute care hospitals in New York was conducted. 57 patients received tPA for presumed PE during March 10th to April 27th. The mean age was 60.8 ± 10.8 years, and 71.9% (41/57) were male. We defined strongly suspected PE among 75.4% (43/57) of patients who had acute worsening of hypoxia and acute hypotension requiring pressors. The findings suggestive of PE included right ventricular (RV) strain in 15.8% (9/57), deep venous thrombosis (DVT) in 7.0% (4/57), increased dead space ventilation (Vd) in 31.6% (18/57) of patients, respectively. RV strain and RV thrombus were present in 3.5% (2/57), RV strain and DVT in 5.3% (3/57), RV strain and increased Vd in 8.8% (5/57), and DVT and increased Vd in 3.5% (2/57) of patients. Chest CT Angiography was not performed in any of the patients. Following tPA infusion, 49.1% (28/57) of patients demonstrated improvement. Six patients (10.5%) survived to discharge, of whom 2 received extracorporeal membrane oxygenation and were transferred to other facilities for lung transplant, 2 were discharged home, and 2 were discharged to a rehabilitation facility. However, overall mortality was 89.5%. The utility of tPA for critically ill patients with COVID-19 and presumed PE warrants further studies.